AKTIVITAS SOSIAL ORANGUTAN (Pongo pygmaeus wurmbii) DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG KABUPATEN KAYONG UTARA KALIMANTAN BARAT - Samhudi, .; Prayogo, Harri; Rifanjani, Slamet (Universitas Tanjungpura, 2019)
Diverse types of habitat were interesting objects which existed in the Cabang Panti Research Station, due to it, the researcher was interested to investigate about Orangutanâ€™s activities in one type of habitat and the researcher focused on Orangutanâ€™s social activities. The purpose of this study was to determine the social behavior of orangutans in the Research Station cabang panti gunung palung national park in Kayong Utara District, West Kalimantan. The used method was focal animal sampling, a method of observing and recording the behavior of one individual over a certain period of time while the object must be visible during observation and the data collection in this study focused on adult male and / or female orangutans as the objects in the study. The length of observation time of the target orangutan in this study wasÂ + 13 hours per day for 5 days by concerning the daily activities of orangutans from waking up to sleeping. Based on the results of the observed object, there were 2 individuals namely Walimah which was an adult female and Julian which was an adult male. Overall, during the observations, the two individuals were following each other, the target orangutan â€œWalimahâ€ had high eating activities throughout the day reaching 41,31% followed by movement activities 25,18%, then resting 23,18%, self-action 9,96%, and social activity 0,37%. While the target orangutan